Interaction of Integrin β4 With S1P Receptors in S1P‐ and HGF‐Induced Endothelial Barrier Enhancement. Issue 6 (June 2014) - Ni, Xiuqin; Epshtein, Yulia; h,; Chen, Weiguo; Zhou, Tingting; Xie, Lishi; Garcia, Joe G.N.; Jacobson, Jeffrey R.
ABSTRACT We previously reported sphingosine 1‐phosphate (S1P) and hepatocyte growth factor (HGF) augment endothelial cell (EC) barrier function and attenuate murine acute lung inury (ALI). While the mechanisms underlying these effects are not fully understood, S1P and HGF both transactivate the S1P receptor, S1PR1 and integrin β4 (ITGB4) at membrane caveolin‐enriched microdomains (CEMs). In the current study, we investigated the roles of S1PR2 and S1PR3 in S1P/HGF‐mediated EC signaling and their associations with ITGB4. Our studies confirmed ITGB4 and S1PR2/3 are recruited to CEMs in human lung EC in response to either S1P (1 µM, 5 min) or HGF (25 ng/ml, 5 min). Co‐immunoprecipitation experiments identified an S1P/HGF‐mediated interaction of ITGB4 with both S1PR2 and S1PR3. We then employed an in situ proximity ligation assay (PLA) to confirm a direct ITGB4–S1PR3 association induced by S1P/HGF although a direct association was not detectable between S1PR2 and ITGB4. S1PR1 knockdown (siRNA), however, abrogated S1P/HGF‐induced ITGB4–S1PR2 associations while there was no effect on ITGB4–S1PR3 associations. Moreover, PLA confirmed a direct association between S1PR1 and S1PR2 induced by S1P and HGF. Finally, silencing of S1PR2 significantly attenuated S1P/HGF‐induced EC barrier enhancement as measured by transendothelial resistance while silencing of S1PR3 significantly augmented S1P/HGF‐induced barrier enhancement. These results confirm an important role for S1PR2 and S1PR3 in S1P/HGF‐mediated EC barrier responses that are associated with their complex formation with ITGB4. Our findings elucidate novel mechanisms of EC barrier regulation that may ultimately lead to new therapeutic targets for disorders characterized by increased vascular permeability including ALI. J. Cell. Biochem. 115: 1187–1195, 2014. © 2013 Wiley Periodicals, Inc.